Time-Varying Impacts of Carbon Price Drivers in the EU ETS: A TVP-VAR Analysis - Li, Peng; Zhang, Hao; Yuan, Yongna; Hao, Aimin (Frontiers in Environmental Science, 2021)
This study analyzes the impacts of different drivers on the pricing of EU carbon futures in various periods by using time-varying parameter vector autoregressive (TVP-VAR) model. The results indicate that: (1) The relationships between oil, gas, electricity, stock and carbon prices have significant time-varying characteristics and that relationship have experienced an inversion in 2016. This might be due to the pressure of achieving the "EU 20-20-20" targets and the signing of the Paris Agreement as well as the fine-tuning of the European Union Emissions Trading Scheme (EU ETS). (2) The impacts of different drivers on carbon price are various. The carbon price is more sensitive to influence oil, gas, electricity and stock prices before the inversion in the short-term, while its response to changes in stock price after the inversion which is more obvious in the mid-long term. (3) After the signing of the Paris Agreement in the second quarter of 2016, the carbon price has a greater response to changes in its drivers. The oil price’s impact on carbon price became the most significantly one among them.